2002
DOI: 10.1007/s00262-002-0312-4
|View full text |Cite
|
Sign up to set email alerts
|

A functional recombinant single-chain T cell receptor fragment capable of selectively targeting antigen-presenting cells

Abstract: Specificity in the immune system is dictated and regulated by specific recognition of peptide/major histocompatibility complexes (MHC) by the T cell receptor (TCR). Such peptide/MHC complexes are a desirable target for novel approaches in immunotherapy because of their highly restricted fine specificity. Recently a potent anti-human p53 CD8(+) cytotoxic T lymphocyte (CTL) response has been developed in HLA-A2 transgenic mice after immunization with peptides corresponding to HLA-A2 motifs from human p53. An alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…HLA class I-associated Ags have also been detected on cells using Abs (15)(16)(17) or Fab monomers/tetramers (18 -20) specific for given peptide-HLA complexes, allowing semiquantitative determination of surface Ag levels by FACS. A similar approach has used soluble monomers (21,22), dimers (23), or tetramers (24,25) of soluble TCRs to detect class I-restricted Ags, although given the naturally low affinity of TCR for Ag, it remains uncertain how quantitative and Ag sensitive such measurements are.…”
mentioning
confidence: 99%
“…HLA class I-associated Ags have also been detected on cells using Abs (15)(16)(17) or Fab monomers/tetramers (18 -20) specific for given peptide-HLA complexes, allowing semiquantitative determination of surface Ag levels by FACS. A similar approach has used soluble monomers (21,22), dimers (23), or tetramers (24,25) of soluble TCRs to detect class I-restricted Ags, although given the naturally low affinity of TCR for Ag, it remains uncertain how quantitative and Ag sensitive such measurements are.…”
mentioning
confidence: 99%
“…In these studies soluble, natural TcRs were fused with an immunomodulatory molecule that redirected the immune system to engage the malignancy. In the first study, exotoxin A was attached to a single-chain TcR and this fusion was shown to selectively kill cells presenting the p53 peptide in vitro [44]. In the second study, interleukin-2 was fused with a single-chain, p53-specific TcR and this fusion was shown to reduce lung metastases in mice [45].…”
Section: Making "Natural" and "Supernatural" Tcrsmentioning
confidence: 99%
“…These receptors could be used as competitive T cell blockers in the treatment of autoimmunity, or for receptor-guided therapies through the artificial attachment of molecular fusion partners for treating malignancies or viral infection. Such fusions could include radionuclides [147], toxins [44], cytokines [45,148,149], mAb fragments [46], gold nanoparticles/nanorods [150,151], viral particules [134], drug-enclosing liposomes [152], and magnetic nanoparticles [153,154]. The attachment of magnetic nanoparticles is of particular interest for immunodiagnostics and immunotherapy [155] since target cells coated in magnetic nanoparticles can be clearly visualized in vivo through magnetic resonance imaging [156,157], and a recent study has claimed that single cell resolution can be achieved [158].…”
Section: Future Directionsmentioning
confidence: 99%
“…However, there are reports of wild‐type single‐chain TCRs fused to, e.g. exotoxin A protein, specifically killing cells presenting p53 peptide antigens [56], and high‐affinity engineering may improve the efficacy of such approaches.…”
Section: Applications Of High‐affinity Tcrs: Cancermentioning
confidence: 99%
“…However, there are reports of wildtype single-chain TCRs fused to, e.g. exotoxin A protein, specifically killing cells presenting p53 peptide antigens [56], and high-affinity engineering may improve the efficacy of such approaches. Fusion of wild-type single-chain TCRs to IL-2 have been reported to reduce lung metastases in an HLA-A*0201 transgenic mouse tumour model [57], and immune effector function may also be provided by fusion to IgG1 H [58].…”
Section: Applications Of High-affinity Tcrs: Cancermentioning
confidence: 99%